RESPON MASYARAKAT TERHADAP PELAYANAN PERNIKAHAN PASCA PEMBERLAKUAN PERATURAN PEMERINTAH NOMOR 48 TAHUN 2014 TENTANG BIAYA NIKAH (STUDI KASUS DI KUA KEC. SELEBAR KOTA BENGKULU) - Heti, Yurda (QIYAS: JURNAL HUKUM ISLAM DAN PERADILAN, 2017)
This research raised  problems response the  public  about  free  and  marriage marriage paid  at  home in the kecamatan kua largest  city bengkulu .The purpose of this study is to find response the  public  about  free and  marriage marriage paid  at home in the  kecamatan kua  largest  city bengkulu .This research use  method juridical  empirical , to technique data collection interview,  chief and documentation, after data obtained were  analysed according to miles and huberman in sugiyono  to analyze  qualitative  may be done  by means reduction the data  reduction) , presentation of the data  display)  , conclusion (verification) , so that it can  be drawn  a conclusion to answer of any the  existing problems. The research showed response the  public  about  free  marriage in the  kecamatan kua  largest  city bengkulu who  gives responnya through  chief and interview  known  that the community kecamatan largest city bengkulu less responding well, this is proven  than 100 % the results  of the answer informants them  do not know  with the establishment of pp .48 2014 that marriage at the kua free then the community kecamatan largest city bengkulu does not agree with marriage at the kua although free this is proven from the answers of the informants 86 % does not agree with marriage at the kua and response the public about  marriage paid at home welcome positive although must spend money  which is not a little .This is proven from the answer chief informants said that they did not mind spent budget  of rp .600,000,—when married at home of 94 %, then the community approve marriage outside the kua equal  to 100 %